Strategies for the implementation of the living guidelines for cochlear implantation in adults - Ramos-Macías, Ángel; De Raeve, Leo; Holcomb, Meredith; Connor, Ella; Taylor, Aiya; Deltetto, Irene; Taylor, Colman (Frontiers in Public Health, 2023)
Clinical guidelines for cochlear implants (CI) exist in several countries, however, they lack consistency and often do not encompass the full user journey. This study aims to explore the barriers and facilitators for implementing global Living Guidelines for cochlear implantation in adults with severe, profound or moderate sloping to profound sensorineural hearing loss (SPSNHL) as well as identify guideline implementation (GI) tools that may support uptake.A convenience sample of Task Force members were recruited for semi-structured interviews. Interview transcripts were thematically analysed to group country-specific barriers, facilitators and GI tools into three levels: health care provider (HCP), consumer and structural. Once identified, barriers and facilitators were classified into four themes related to awareness, economic, guideline or other.Interviews were conducted with 38 Task Force members, representing 20 countries. Lack of CI and hearing loss awareness was a major barrier at the HCP (85% of countries), consumer (80%) and structural (20%) levels. Economic and guideline barriers followed at the HCP (35%; 25%), consumer (45%; 0%) and structural (55%; 30%) levels, respectively. Facilitators focused on raising awareness of hearing loss and CIs as well as guideline related initiates at the HCP (80%; 70%), consumer (70%; 10%) and structural (25%; 70%) levels. GI tools including education, economic evaluations, quick reference resources and social media can help improve awareness and uptake.Awareness is the primary barrier to implementing Living Guidelines globally for adults with SPSNHL. Endorsement from key professional bodies and using the best available evidence can enhance uptake.